ANALISIS MANAJEMEN OPERASIONAL DALAM PROGRAM JEMPUT ZAKAT DI LAZNAS AL IRSYAD PURWOKERTO - Difa Anggry Fardiana; Hilmi Romadon; Kaila Raihannisa; Mahardhika Cipta Raharja (CV. Denasya Smart Publisher, 2026)
This study aims to analyze the operational management of the zakat pick-up service program at LAZNAS Al Irsyad Purwokerto as a direct service-based strategy for zakat collection. The background of this study is based on the collection of zakat which is still suboptimal compared to its potential, highlighting the need for more effective and responsive service innovations. This research employs a qualitative approach with a descriptive design. Data were collected through in-depth interviews, observation, and documentation involving institutional managers, field officers, and muzakki. Data analysis was conducted using the Miles and Huberman model, including data reduction, data display, and conclusion drawing, while validity was ensured through triangulation and member checking. The findings indicate that the operational management of the zakat pick-up program has been implemented through systematic planning, execution, and evaluation stages. However, several challenges remain, including limitations in human resources, service coverage, and operational efficiency. The program has proven to enhance convenience for muzakki and increase trust in the institution, thereby contributing to improved zakat collection. This study contributes to the development of operational management in zakat institutions, particularly in direct service-based collection strategies and for improving service effectiveness of zakat institutions.